Web-based internship recommendation system for FSKM degree student using rule-based technique / Maslinda Zakaria - Zakaria, Maslinda (2019)
Recommendation system are commonly used to guide someone to find what they want that fit with their personal preferences. Nowadays, many students got opportunity to choose their internship based on their own preferences. They had a problem to choose an internship placement because some student does not get what they had chosen. Many companies had listed their internship programs and open position in their website, which is give student a way to explore it. But, some student does not explore it and just choose it without checking what position they had apply. Therefore, it is essential to have an internship recommendation to provide satisfied result for student when searching their internship placement based on the skill, interest and location. This paper proposed to develop a web-based internship recommendation system using rule-based approach. The goal of this project is to help the student searching the internship placement effectively. Rule-based approach is being used in this recommendation system, where all the data are being collected based on the student preferences. Then, the rules will generate final outcome which recommend the suitable internship placement to a student. The result shows the functionality of this system has been achieved and works well. This study is significantly helping the students to choose their internship placement.